Reality Counseling Effectiveness Modeling Techniques to Improve Characterable to Talk with Stunning through Lesson Study Class X Iis 2 Undiksha Laboratory High School Singaraja - Made Indah Dewi; I Kadek Suranata; I Ketut Dharsana (International Conference on Technology and Educational Science)
This study aims to determine the effectiveness of behavioral counseling by modeling techniques to improve the characterable to talk to cutethrough the study of the lessons in the first grade students. This type of research is quasi-experimental with pre-test and post-test control group design. A sample of 22 students with df 21. Methods of data collection using questionnaires character can talk to cute 30 items. The results of the data analysis is the value2.77 > 2.07 ttable so Ho rejected and Ha accepted. So there is a significant difference. It can be concluded that the effectiveness of counseling reality by modeling techniques to improve the characterable to talk to cute.